The Anatomy of Human Destructiveness - Fromm Erich (Penguin Books)
A major work of argument and reflection on human aggression. Preface, Terminology, Introduction: Instincts and Human Passions, Instinctivists and Behaviorism and Psychoanalysis, The Instinctivists, Environmentalists and Behaviorists, Instinctivism and Behaviorism, Malignant Aggression: Cruelty and Destructiveness, Malignant Aggression: Necrophilia, Malignant Aggression: Adolf Hilter - a Clinical Case of Necrophilia, Epilogue: On the Ambiguity of Hope, Freud's Theory of Aggressiveness and Destructiveness, Bibliography, Index.